Human resource management current directions and new challenges : with overview of international HRM - Mendoza, Ernesto H.; Garcia, Lorma S.P (Unlimited Books Library Services and Publishing, 2019)
Human resources management is the strategic and coherent approach to their valued assets, it's people. This book is designed to contribute in a modest way, more insights in the field of managing people.